Efeito do ambiente térmico sobre características de pelame e parâmetros fisiológicos de vacas Nelore e Nelore x Araguaia - Santos, Douglas Borges (2015)
This study aimed to investigate the effects of thermal environment than two regions of the Brazilian Cerrado on physiological parameters and hair coat characteristics of Nelore cows and cows from the cross Araguaia race. It was evaluated 80 Nellore cows and 40 cows from the crossing Araguaia race in February and July: 40 Nellore and 40 Araguaia in Santa Rita farm, at Torixoréu-MT, and 40 Nellore cows in Capim Branco farm, at Uberlândia-MG. The physiological parameters evaluated were respiratory rate, surface temperature, rectal and epidermis. The hair coat characteristics were coat thickness, length, number and inclination of hair (IP). These were compared using the Tukey, Kruskal-Wallis and Mann-Whitney tests and the correlations were estimated by the Pearson method. Comparing the Nellore cattle between the two regions was observed that temperature of the body surface and the epidermis did not differ in two periods and areas surveyed, except for a reduction in the body surface temperature in July at Uberlândia. This breed showed no difference in rectal temperature between two periods of the year, but in February, the value found in Uberlândia was lower than that obtained in Torixoréu. Respiratory rate of Nellore cows from Uberlândia was higher in February compared with July. The hair coat thickness and the inclination of hair had no difference between the periods of collection, but differed by region. The variable number of hair had no difference between the regions in the two periods, except in February in the region of Torixoréu, where animals showed low for the number of hair compared to other regions and periods of year. When comparing Nellore cattle with animals from the Araguaia race it was not observed difference (P>0.05) between the rectal, surface and epidermis temperatures in different breeds and periods. Respiratory rate of Araguaia rce was higher in July. The coat thickness and number of hair showed no significant difference between the animals, being observed a reduction in the number of hair in February. It was also observed that the Araguaia race showed a greater length of hair compared to Nellore and a lowest inclination of hair in February. The two regions influenced the most of hair coat characteristics and physiological parameters of Nellore cows in both periods, but the animals maintained body temperature within the average for the breed, demonstrating the adaptation of animals to the Cerrado. It can also be concluded that the Araguaia race, despite having two European breeds in the genetic composition, has thermoregulation characteristics similar to Nellore.